ANALYSIS OF FARMERS’ PERCEPTION OF RECOMMENDED EXTENSION PACKAGES ON SELECTED CROPS IN YOBE STATE, NIGERIA - Babaji, A. U.; Danwanka, H. A.; Iliyasu, Y. (Journal of Agripreneurship and Sustainable Development, 2018)
The study analyses farmers’ perception of recommended extension packages on selected crops in Yobe State, Nigeria. Multistage random sampling technique was used to select 230 respondents for the study. Structured questionnaire were used to elicit information from the respondents. Data obtained were analyzed using descriptive statistics and multiple regression analysis. The respondents were within the mean age of 36 years, with the mean house hold size of 5 persons. The respondents had the mean farm size of 2 ha and the mean farming experience of 16 years. Majority (87.0%) of the respondents were male. Majority (48.5%) of the respondents in the study area were contacted and taught by extension agents based on group teaching method. Majority (56.1%) of the farmers expressed opinions that administrations of agricultural extension activities in the study area were either very effective or effective. Most (71%) on average of the respondents used the nine (9) improved farm practices introduced to them frequently. Most (82.6%), (90.9%) and (80.9%) of the respondents had increase in yield of sorghum, millet and cowpea, respectively. Majority (40.0%) of the respondents in the study area had participated in project meeting and field days and majority (56.1%) of the respondents were visited once a month by the extension agent. The result of multiple regression analysis showed that variables such as farmers’ age, farm size, level of education, visit by extension personnel, participation in project activities, farming experience and household size were positive and significantly influence the level adoption to extension recommendations at ( p<0.05, p<0.05, p<0.001, p<0.001, p<0.001, p<0.001 and p<0.01), respectively. Majority (61.8%) of the respondents discovered that lack of necessary inputs were the most serious problems responsible for some farmers in the study area not adopting the improved farm practice introduced to them. The study, therefore, concludes that agricultural extension activities were found effective in the study area and the adoption of improved farm practices introduced to the farmers by the agricultural extension agents led to increase in sorghum, millet, and cowpea productivity in the study area. Based on this study, it was recommended that, Government should provide the farm inputs to farmers at subsidized prices and at the right time.